PERBANDINGAN GAYA FRIKSI BUSUR STAINLESS STEEL PADA BRAKET BEGG, EDGEWISE PREADJUSTED, DAN SELF-LIGATING - GUNAWAN, KRISTINA WIJAYA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Friction that occurs on bracket and archwire interface greatly affect tooth movement. Ligation types, slot size, bracket wide, and archwire size can affect frictional force. The objectives of this study was to compare frictional force of Begg, conventional preadjusted Edgewise, and self-ligating brackets using stainless steel archwire. This study used stainless steel archwires on Begg, conventional preadjusted Edgewise, and self-ligating brackets. Fourty samples were divided by 4 groups: Begg bracket with safety-lock pin, Begg bracket with regular-lock pin, conventional preadjusted Edgewise, and self-ligating brackets group. Each group was further divided by 2 groups, 5 samples was tested with 0.016 inch stainless steel archwires and the others with 0.020 inch. Friction was measured using Universal Testing Machine. The data were tested by 2-way analysis of variance. The results showed that there was statistically significant difference of friction because of bracket types and archwire sizes and the interaction between the use of bracket types and archwire sizes (p<0.05). The conclusions were there was difference frictional force of Begg, conventional preadjusted Edgewise, and self-ligating brackets using stainless steel archwire with the lowest friction was self-ligating brackets using 0,016 inch stainless steel archwire and the highest was Begg bracket with regular-lock pin using 0,020 inch stainless steel archwire.